INTRA-OPERATIVE STIMULATION OF MEDIAN NERVE REDUCES THE RISK OF POSTOPERATIVE NAUSEA AND VOMITING AFTER POSTERIOR FOSSA MASS RESECTION - А. S. Kulikov; M. I. Klyukin; I. M. Belisov; А. Yu. Lubnin (Вестник анестезиологии и реаниматологии, 2019)
The article presents the results of a prospective randomized double-blind study which was investigating the efficacy of intra-operative transcutaneous stimulation of median nerve on the wrist aimed to prevent post-operative nausea and vomiting after planned resection of brain tumors located in posterior fossa.Methods. 40 patients were included into the study: 20 patients were enrolled into the stimulation group and 20 of them were enrolled into the control group, where the prevention of emetogenic reactions was limited by the use of dexamethasone and ondansetron.Results. The demographic and clinical parameters were compatible in the both groups. During the first 12 hours after recovery, the risk to develop symptoms was significantly lower in the stimulation group (p <0.05): 7 cases versus 14 ones in the control group (RR =0.5; 95% CI 0.26−0.97) and 4 versus 10 cases of vomiting in the control group (RR =0.4; 95% CI 0.15−1.07). No side effects were observed.Conclusion. It was confirmed that this method was effective to prevent postoperative nausea and vomiting in the patients who underwent infratentorial craniotomy.